Термооптимум и термостабильность пектинметилэстеразы и полигалактуроназы ферментного препарата из люцерны - Безусов, А. Т.; Никитчина, Т. И. (НТУ "ХПИ", 2015)
Исследовано влияние температуры на скорость ферментативных реакций при воздействии пектинметилэстеразы и полигалактуроназы ферментного препарата люцерны. Потенциометрическим методом определили влияние температуры на стабильность фермента, скорость распада фермент-субстратного комплекса и сродство фермента к субстрату. Полученные данные свидетельствуют о стабильности ферментов, выделенных из люцерны. Этот показатель превышает данные препарата микробиологического происхождения "Пектофоєтидин П20х", что позволяет проводить ферментативную реакцию при высоких температурах, повышая технологические свойства растительного фермента.

Most necessary for industry along with amylolytic and proteolytic enzymes there are enzymes of pectolytic complex. In modem technologies of food productions enzymes preparations with pectolytic activity found application in the technological operations of lighting up of juices (apple, vine, pear), and also at the production of juices with pulp (citrus, plum, tomato), that does them irreplaceable at processing of berries, fruit, vegetables. In basis of their use in technologies ability of deeterificashon lies and to depolymerize a pectin (pectinasa and pectaza accordingly). The use of the enzymes preparations with pectolytic activity, got by a microbiological synthesis, is wide in modem technologies. Source of such preparations are genetically modified mycelia mushrooms. Practically all products of microbial biotechnology can contain undesirable elements are by-products of vital functions of microorganisms, and require an obligatory certification and examination. Research of alternative pectolytic enzymes of grassy culture is alfalfas, allows to get clean preparations ecologically. Experiments showed that influence of temperature on stability of enzyme, speed of disintegration of enzyme-substance complex and affinity of enzyme to substance exceed data of preparation of microbiological origin of "Pectofoetidin P20x", that allows to conduct a enzymes reaction at high temperatures, promoting technological properties of vegetable enzyme. The conducted analysis allowed estimating as far as sharply a necessity costs for the industrial receipt of enzymes preparations of phytogenous.
Temoptimum and thermostability of pectin methylesterase and polygalacturonase of enzymatic preparations from alfalfa
Keywords: температура; пектин; потенциометрический метод; фермент-субстратный комплекс; растительный фермент; temperature; ebzyme-substance complex; vegetable enzyme